The Characteristics of Morphometric Enhalus acoroides in the Seagrass beds of Malahing Village, Bontang City - Putri, Niken Astrid Pradiva; Irawan, Aditya; Sari, Lily Inderia (Jurnal Biologi Tropis, 2025)
Seagrass beds are macro and micro habitats for marine aquatic biota. The habitat characteristics formed by seagrass beds are closely related to the species and morphometrics of the species. Enhalus acoroides is a seagrass species that has larger root, rhizome, and leaf morphometrics compared to other seagrass species. This study aims to determine the morphometric characteristics of E. acoroides in the seagrass beds of Malahing Village, Bontang City, East Kalimantan Province. This study was conducted from October 2024 to February 2025. Data collection of E. acoroides, water samples and bottom substrates used a purposive sampling approach divided into 4 stations with 3 replications. Sampling of E. acoroides density used a 50x50cm square frame. Each sample of E. acoroides stands was subjected to morphometric measurements. The density of E. acoroides in the seagrass beds of Malahing Village in the density criteria, the morphometric characteristics of leaves, rhizomes and roots were relatively smaller and associated with the sand bottom substrate.